Signs of recovery: Patterns of livelihoods and food security before and during COVID-19 in rural Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Gilligan, Daniel O.; Hoddinott, John F.; Roy, Shalini; Anowar, Md Sadat; Ghostlaw, Julie; Thai, Giang (International Food Policy Research Institute, 2021)
The COVID-19 pandemic compelled the Government of Bangladesh to impose measures to stop the spread of the virus. These efforts were critical for public health, but have led to serious disruptions in the economy and livelihoods. To document the experiences of Bangladeshi households during this time, the International Food Research Institute (IFPRI) and Cornell University conducted two rounds of socioeconomic phone surveys in rural areas of Bangladesh in June 2020 and in January 2021, and benchmarked them against data from in-person interviews carried out on the same households in 2019. Together, these surveys have tracked the experiences of Bangladeshi households in terms of unemployment, income loss, food insecurity, and coping mechanisms during the COVID-19 pandemic.